2002
DOI: 10.1001/archinte.162.7.792
|View full text |Cite
|
Sign up to set email alerts
|

Can a Back Pain E-mail Discussion Group Improve Health Status and Lower Health Care Costs?

Abstract: An e-mail discussion group can positively affect health status and possibly health care utilization. It may have a place in the treatment of chronic recurrent back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
0
20

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 16 publications
2
166
0
20
Order By: Relevance
“…More generally, studies have suggested that such material can improve compliance [15], alleviate anxiety and promote psychological well being [23], and reduce medical negligence claims [39]. Although other media including video and internet have been explored [9,19,41], written material is by far the simplest, cheapest and therefore potentially the most cost-effective method [38]. However, developing acceptable and effective informational material is not easy, even for the apparently simple medium of booklets or leaflets [3,12,20].…”
Section: Discussionmentioning
confidence: 99%
“…More generally, studies have suggested that such material can improve compliance [15], alleviate anxiety and promote psychological well being [23], and reduce medical negligence claims [39]. Although other media including video and internet have been explored [9,19,41], written material is by far the simplest, cheapest and therefore potentially the most cost-effective method [38]. However, developing acceptable and effective informational material is not easy, even for the apparently simple medium of booklets or leaflets [3,12,20].…”
Section: Discussionmentioning
confidence: 99%
“…Two trials evaluated internet-based brief interventions (Buhrman et al 2004, Lorig et al 2002. One examined the use of a closed, moderated, e-mail discussion group in people with chronic back pain having at least 1 outpatient visit in the past year, no "red-flag" symptoms, and access to e-mail (Lorig et al 2002).…”
Section: Effectiveness Of Minimal Contact (Internet-based) Interventimentioning
confidence: 99%
“…One examined the use of a closed, moderated, e-mail discussion group in people with chronic back pain having at least 1 outpatient visit in the past year, no "red-flag" symptoms, and access to e-mail (Lorig et al 2002). Participants also received a book and videotape about back pain.…”
Section: Effectiveness Of Minimal Contact (Internet-based) Interventimentioning
confidence: 99%
“…34 Lorig and her group have also explored more innovative group formats, such as e-mail discussion groups. 35 One year of participation in e-mail groups produced improvements in health status (pain, role function, and health distress) and a trend toward decreased physician visits.…”
Section: Studies Examining Group Programsmentioning
confidence: 99%